PENGARUH KUALITAS AUDITOR, KOMITE AUDIT, AUDIT DELAY, AUDIT TENURE TERHADAP KUALITAS AUDIT - andy wijaya (Fakultas Ekonomi Prodi Akuntansi, 2022)
The purpose of this study is to examine and analyze whether the quality of the auditor, audit committee, audit delay and audit tenure affect audit quality. This study uses a banking population listed on the BEI amounting to 45 banks, and a sample that meets the criteria as many as 43 banks. The technique used to analyze observation data is logistic regression with SPSS 21 application. From the test results, it can be concluded that partially or simultaneously the quality of auditors, audit committees, audit delay and audit tenure does not affect audit quality in the banking sector. The value of Nagelkerke's R Square obtained is 0.065 or 6.5%.